2021
DOI: 10.7759/cureus.14118
|View full text |Cite
|
Sign up to set email alerts
|

Extensor Tendon Rupture After Distal Radioulnar Joint Surgery: A Case Series

Abstract: Symptomatic arthritis of the distal radioulnar joint (DRUJ) is often treated nonoperatively but with persistent symptoms may be treated surgically with partial or complete distal ulna resection. In many of these cases, ulna resection in combination with tendon reconstruction can successfully restore hand function. We identified three patients who underwent the Darrach procedure to treat DRUJ arthritis that developed attritional ruptures due to sharp prominent bone edges or dorsal capsule disruption. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Yamazaki H et al reported tendon ruptures in 37 patients with osteoarthritis, noting an increased risk of tendon rupture with associated scallop sign (sclerotic border of the ulnar aspect of distal radius), dorsal inclination of the sigmoid notch, and radial shift of the ulnar head relative to the radius. Case reports have also reported attritional extensor tendon ruptures in distal ulnar resection for DRUJ arthritis [ 12 , 13 ], scaphoid nonunion advanced collapse (SNAC) wrist [ 14 ], and Kienbock's disease [ 15 ]. Traumatic, non-arthritic tendon injuries most often result from incidents involving sharp objects or saws, typically affecting the dominant hand [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamazaki H et al reported tendon ruptures in 37 patients with osteoarthritis, noting an increased risk of tendon rupture with associated scallop sign (sclerotic border of the ulnar aspect of distal radius), dorsal inclination of the sigmoid notch, and radial shift of the ulnar head relative to the radius. Case reports have also reported attritional extensor tendon ruptures in distal ulnar resection for DRUJ arthritis [ 12 , 13 ], scaphoid nonunion advanced collapse (SNAC) wrist [ 14 ], and Kienbock's disease [ 15 ]. Traumatic, non-arthritic tendon injuries most often result from incidents involving sharp objects or saws, typically affecting the dominant hand [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar mechanism was described by Fletcher C et al, where they demonstrated an extensor tendon rupture following distal radius excision. This rupture was attributed to a prominent dorsal distal ulna causing direct irritation to the extensor tendon, leading to an attritional rupture [ 12 ]. Similarly, in this case, we propose that the attritional EDM rupture was likely caused by the EDM tendon abutting the distal ulna fracture, resulting in direct tendon irritation and subsequent rupture.…”
Section: Discussionmentioning
confidence: 99%
“…This typically involves partial or complete distal ulnar resection and may be performed in combination with tendon reconstruction if extensor tendon rupture had occurred, as in our patient presented. There have also been case reports of extensor tendon rupture occurring post-operatively [9]. Fletcher et al recommend various intra-operative steps that may be undertaken to minimize the risk of this complication.…”
Section: Discussionmentioning
confidence: 99%
“…Fletcher et al recommend various intra-operative steps that may be undertaken to minimize the risk of this complication. This includes ensuring that the resected distal ulnar stump is smooth, that the DRUJ is free of bony prominences, that any capsular deficiencies are reconstructed, that the distal ulna and DRUJ are stabilized intra-operatively, and that the extensor tendons are able to move freely [9].…”
Section: Discussionmentioning
confidence: 99%